2020
DOI: 10.1177/1938640019895919
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Flexor Hallucis Longus Transfer for Achilles Noninsertional Tendinopathy: Description of Surgical Technique and Functional Outcomes

Abstract: Background. The transfer of the flexor hallucis longus (FHL) tendon is an established treatment for replacing a dysfunctional Achilles tendon. Objectives. (1) Describe a new technique for endoscopic FHL transfer for noninsertional Achilles tendinopathy and (2) describe the functional outcomes and complications after endoscopic and open FHL transfer. Materials and Method. Retrospective study of patients who underwent open or endoscopic FHL transfer between 2014 and 2016. The American Orthopaedic Foot & Ankl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Furthermore, 3 of the studies reported a statistically significant improvement in pain, function, and activity level. 20 - 22 In the Schon et al 23 study, the VAS pain scores and the Ankle Osteoarthritis Scale pain scores decreased a statistically significant amount, and the 36-Item Short Form Survey scores increased a statistically significant amount following FHL transfer. However, a fairly high number of complications (27.1%) were reported.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, 3 of the studies reported a statistically significant improvement in pain, function, and activity level. 20 - 22 In the Schon et al 23 study, the VAS pain scores and the Ankle Osteoarthritis Scale pain scores decreased a statistically significant amount, and the 36-Item Short Form Survey scores increased a statistically significant amount following FHL transfer. However, a fairly high number of complications (27.1%) were reported.…”
Section: Resultsmentioning
confidence: 97%
“…2). This core domain included measures relating to return to activity, including sports (18 studies) [14,19,22,87,98, [169,258,275,284]. The most commonly reported measurement instrument was the Tegner Score (five studies) [13,111,121,205,308].…”
Section: Participationmentioning
confidence: 99%
“…'Clinical examination findings' included various measures such as swelling (five studies) [14,18,45,137,284] and calf circumference (four studies) [197,200,212,216].…”
Section: Achilles Tendinopathy Specific Domainsmentioning
confidence: 99%